CARBON EMISSION DISCLOSURE AND FINANCIAL PERFORMANCE: STUDY ON COMPANIES LISTED IN JAKARTA ISLAMIC INDEX (JII) 2014-2018 - Rahmawati, Fitri (At-Taradhi Jurnal Studi Ekonomi, 2020)
This study aims to find out empirically the effect of Carbon Emission Disclosure and Financial Performance study on companies listed in Jakarta Islamic Index (JII) 2014-2018. This research uses quantitative research methods, using panel data analysis. Data collection uses secondary data from documentation related data. Data is taken from annual report and sustainability report of each variable from 2014-2018. In addition, there are control variables in this study, namely leverage, industry type and size. The research test uses the t test and F test and is processed using Eviews8. The results showed that Return on Asset (ROA) and Return on Equity (ROE) has a positive and significant impact on Carbon Emission Disclosure (CED). However, the variable Earning Per Shares (EPS) not have significant influence on Carbon Emission Disclosure (CED). The Results showed that Return on Asset (ROA), Return on Equity (ROE), and Earning Per Shares (EPS) had a significant simultaneous effect on the Carbon Emission Disclosure (CED).